2016
DOI: 10.1016/j.tourman.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Experiential places or places of experience? Place identity and place attachment as mechanisms for creating festival environment

Abstract: Tourism theory suggests mechanisms of place are critical in the construction of tourism environments. However, contradictory place theory has created confusion as to exactly what these mechanisms are and how they affect perceived environment. Literature identifies place attachment and place identity as primary mechanisms in the construction of tourist relationships with tourist environments. An interpretive methodology is used to explore these mechanisms during a festival experience, and thematically analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 50 publications
6
72
0
7
Order By: Relevance
“…For example, Brady, Voorhees, and Brusco, (2012) found that after receiving useful information and knowledge from other customers, a customer tends to reciprocate more with other customers during his/her time staying and interacting with a focal service. However, empirical studies into the effect (Davis, 2016). Therefore, place attachment in the current study refers to a person's psychological attachment to an event or a festival.…”
Section: Festivalscapementioning
confidence: 99%
“…For example, Brady, Voorhees, and Brusco, (2012) found that after receiving useful information and knowledge from other customers, a customer tends to reciprocate more with other customers during his/her time staying and interacting with a focal service. However, empirical studies into the effect (Davis, 2016). Therefore, place attachment in the current study refers to a person's psychological attachment to an event or a festival.…”
Section: Festivalscapementioning
confidence: 99%
“…Simultaneously noted however is the expansion of conservation, green, eco and simple tourism movements, as well as growing demand for deeper, more meaningful, involved and co-created experiences (i.e. Davis, 2016;MacCannell, 2002;Richards, 2011). These types of tourism may not be ego-free (Wheeller, 2005), but they in some forms at least suggest a less self-centric, superficial or narcissistic focus.…”
Section: Introductionmentioning
confidence: 99%
“…The immersive and non-routine experience allows for the unfolding of the relationship between an individual and the environment, enabling the development of meaningful interactions between the two parties (Davis, 2016). Tourist environmental aspects include various natural and man-made elements as the geographical dimension (space and place) (Pearce, 2014), servicescape, hardware, and service systems (Komppula, Ilves, & Airey, 2016), design attractiveness, layout/ease of navigation, upkeep and physiological ambience (Walls, 2013), signs and visual communication (Tussyadiah & Fesenmaier, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The environmental attributes allied to management decisions are mediators of the destination experience, besides the destination choice present a significant influence on the likelihood of a satisfying experience (Breejen, 2007). Relationships between tourists and the environment are built through attachment and feeling of belonging to a place (Davis, 2016).…”
Section: Discussionmentioning
confidence: 99%